2014
DOI: 10.1355/ae31-3e
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Capital Structure of Listed Vietnamese Companies

Abstract: This paper provides the first insights into the capital structure of listed companies in Vietnam, one of the most dynamic economies in the Asia-Pacific region. We employ a panel GMM (generalized method of moments) system estimator to analyse the determinants of the capital structure of non-financial firms listed on either the Ho Chi Minh Stock Exchange or the Hanoi Stock Exchange for the period 2007–11. We conclude that, despite the emergence in recent years of equity and a corporate debt capital market, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
4
7
0
Order By: Relevance
“…PVAR estimates indicated a positively and highly significant impact over performance confirming the findings of López and Lima [42] and De Bandt et al [6] but contradicting those of Nawaz et al [5] and Nguyen et al [60]. Correlation values confirmed this positive effect over ROE [6] but revealed a negative coefficient between Fin.…”
Section: Analysis and Results Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…PVAR estimates indicated a positively and highly significant impact over performance confirming the findings of López and Lima [42] and De Bandt et al [6] but contradicting those of Nawaz et al [5] and Nguyen et al [60]. Correlation values confirmed this positive effect over ROE [6] but revealed a negative coefficient between Fin.…”
Section: Analysis and Results Discussionsupporting
confidence: 73%
“…Through correlation analysis, Biger et al [54] found that financial leverage in Vietnamese firms decreases with profitability. Similar results were found: in a study by Al-Qaisi [55] which collected data from United Arab Emirates; Majumdar and Chhibber [56] who used data from Indian firms; Nguyen and Neelakantan [57] who used data collected by the International Finance Corporation (IFC) from 10 developing countries; Huang and Song [58] and Chen [59] who used Chinese companies; Gill and Mathur [47] for manufacturing firms; Nguyen et al [60] for Vietnamese listed firms; and Nawaz et al [5] for Pakistani firms.…”
Section: Literature Review and Analysis Of Interactions Between Factorssupporting
confidence: 78%
“…A survey by the GSO in April 2020 documented that, due to the impact of the pandemic, 66.8% of Vietnamese firms had to reduce salary expenses, of which 39.5% of firms let their employees take turn to work, 28.4% laid off their employees, 21.3% imposed unpaid leave and 18.9% had salary cut (GSO, 2020a). The liquidity problem of Vietnamese firms is more severe given the fact that firms rely heavily on short-term financing sources (Nguyen et al, 2014). Altogether, these suggest a lack of financial stability amongst Vietnamese firms.…”
Section: The Financial Situation Of Vietnamese Firms During Covid-19 Pandemicmentioning
confidence: 99%
“…Regarding the context of transitional economies such as Vietnam, the ownership structures could play an important role in firms' governance and performances (Guan et al, 2021). Finally, previous literature on Vietnamese firms (Vo and Ellis, 2017;Nguyen et al, 2014) tends to support the detrimental effect of debt financing on firm performance. As a new appROAch, we focus on the non-linearity in this study.…”
Section: Introductionmentioning
confidence: 98%